Poverty across various canal commands in irrigated Punjab, Pakistan - Muddasser, Muhammad; Jehangir, Waqar A.; Hussain, Intizar; Ashfaq, Muhammad (2004)
Agricultural income occupies significant share of rural households? income. Only ample and reliable supplies of surface irrigation water can guarantee its improvement. As poverty is inversely correlated with improvement in incomes, provided other factors remain the same, the policy makers can use irrigation as a tool in poverty reduction programs. The inequity in surface water distribution not only affects the rural households across different irrigations but also influences the distribution of income and poverty situation in different reaches of each irrigation system. Since long, it is asserted that households in the tail reach areas have relatively poor access to irrigation water as compared to those situated in the head and middle reach areas. It is evident that more distance from irrigation source brings more households in the poverty trap are located at the tail reach area. Here, the intensity of poverty would be higher than in the head and middle reach areas. This paper tests this hypothesis with results showing that poverty increases in the tail reach areas as compared to head and middle reach areas. This calls for the need to address current hurdles exercising equity and reliability in irrigation supplies in order to provide this vital input for increasing agricultural productivity of the tail end farm households.